Pancreatic Metastasis from Adenocarcinoma of the Uterine Cervix - Do Jun Kim (The Korean Journal of Gastroenterology, 2019)
Pancreatic metastasis from cervical cancer is extremely rare. We report a case of metastatic adenocarcinoma of the pancreas from uterine cervical cancer. A 70-year-old woman was referred because of a pancreatic mass detected by CT. She had been diagnosed with uterine cervical adenocarcinoma 20 months previously. After concurrent chemoradiotherapy, CT showed no evidence of the cervical mass, and follow-up showed no evidence of recurrence. Endoscopic ultrasound-guided fine needle aspiration biopsy of the pancreatic mass resulted in a diagnosis of metastatic adenocarcinoma from uterine cervix.